Reducing work-related Musculoskeletal Disorders (MSDs) through design: Views of ergonomics and design practitioners. - Punchihewa, Himan K. G.; Gyi, Diane E. (Work, 2016)
BACKGROUND: Work-related Musculoskeletal Disorders (MSDs) affect the well-being ofworkers. Unfortunately, user requirements for design to reduce workplace risk factors for MSDs are not always effectively communicated to designers creating a mismatch between the user requirements and what is ultimately produced. OBJECTIVE: To understand the views of practitioners of design and ergonomics regarding tools for participatory design and features they would like to see in such tools. METHODS: An online questionnaire survey was conducted with a cohort of practitioners of ergonomics and design (n = 32). In-depth interviews were then conducted with a subset of these practitioners (n = 8). To facilitate discussion, a prototype integrated design tool was developed and demonstrated to practitioners using a verbalized walkthrough approach. RESULTS: According to the results of the questionnaire survey, the majority (70%) believed an integrated approach to participatory designwould help reducework-related MSDs and suggestedways to achieve this, for example, through sharing design information. The interviews showed the majority (n = 7) valued being provided with guidance on design activities and ways to manage and present information. CONCLUSION: It is believed that an integrated approach to design in order to help reducework-related MSDs is highly important and a provision to evaluate design solutions would be desirable for practitioners of design and ergonomics.